Motor and Bearing Temperature Monitoring of Milling Machine Based on Plc-Scada - Angreine Stevia Singal; Sweetstory Josefard Regar; Lorena Rima Aneru; Antonius P.G. Manginsela; Marson James Budiman (International Journal Labs, 2026)
This study addresses the growing need for reliable thermal monitoring systems in industrial milling machines, particularly for spindle motors and bearings that are highly vulnerable to overheating during continuous machining operations. Excessive temperature can reduce component lifespan, increase maintenance costs, and cause unexpected production downtime. Therefore, this research aims to design and evaluate a PLC-SCADA-based temperature monitoring system capable of providing real-time monitoring, automatic alarm response, and historical data logging for milling machine operation. The research employed an experimental engineering approach using a Siemens S7-1200 PLC integrated with PT100 RTD temperature sensors, Modbus TCP/IP communication, and SIMATIC WinCC Flexible SCADA software. Four PT100 sensors were installed on the spindle motor and bearing housings to acquire thermal data continuously during idle, medium-load, and full-load machining conditions. The results demonstrated that the system successfully monitored temperature in real time with a SCADA update latency below 200 ms and communication latency averaging 3.6 ms. The maximum spindle motor temperature reached 98.4°C during full-load operation, while the implemented warning and automatic cooling system successfully prevented critical overheating conditions. Temperature measurement accuracy achieved a mean absolute error of 0.41°C compared with the reference instrument. In conclusion, the proposed PLC-SCADA monitoring system effectively improves machine reliability, operational safety, and predictive maintenance capability in industrial milling machine applications.